Manajemen Persatuan Bola Basket Seluruh Indonesia (PERBASI) Kabupaten Tanggamus - Siswoyo, Joan; Cahyadi, Ardian; Wicaksono, Lungit (Journal Sport Area, 2020)
This study aims to produce: (1) Model of management program implementation in PERBASI (Indonesian Basketball Association) Tanggamus Regency, (2) Model of management system and basketball coaching in PERBASI Tanggamus Regency. This is a qualitative research study looking at different aspects of sport organization in this region. The research subjects are: (1) Branch manager of PERBASI Tanggamus (2) Manager of PERBASI Tanggamus (3) Sports agencies in the Tanggamus Regency, (4) athletes, coaches, communities. Data collection was performed by using observation, interviews and documentation. The data analysis technique used was triangulation. The results showed that: (1) Branch manager of PERBASI in carrying out organizational management does not have a system of implementing the program, (2) The basketball coaching system at Tanggamus has not been designed to be sustainable, (3) The sports coaching system at Tanggamus is not running optimally. The management system of the organization, basketball and sports in Tanggamus Regency is not yet running well. Based on the results, it proposes an ideal model of sports management (1) the ideal model of basketball management in PERBASI Tanggamus, (2) the ideal model of a management system. The conclusion of the research states that the implementation of basketball management and coaching in Tanggamus Regency has not been programmed efficiently. Results of this research suggest that all parties involved in a basketball sports coaching system in Tanggamus Regency should cooperate in implementing management programs.